Experimental Study on High Strength Concrete by Partial Replacement of Fine Aggregate by Ceramic Tile waste - Dhanasekar, S; Vinothraj, S; Ravichandran, P T; Aravindan, A (International Journal of Engineering and Technology, 2018)
Growth in construction industry is linked to the growth of infrastructure sector and the building industry.Â  Construction industry has been growing @ 8-10% per annum and is likely to maintain the same in year to come. Concrete is widely used as a construction material due to inherent advantages. Booming economic growth led to indiscriminate and unregulated mining of river sand for construction which resulted in erosion of river bank and damage to bio-diversity. The demand for river sand is only expected to grow as the demand for housing and infrastructure is ever increasing. Hence, there is a pertinent need to look for alternate materials to river sand.This study explores use of ceramic tile waste as an optionto the replacement of river Sand in terms of suitability, acceptability, and viability. In this study the ceramic tile waste is being used to replace the conventional sand i.e. fine aggregate (FA). The ceramic fine aggregate (CFA) are used in concrete by replacing FA by 10%, 20%, 24%, 28%, 30% and 40%. In order to compare the results of conventional concrete (CC) with CFA concrete a concrete design mix of M50 is produced with various proportions of CFA material. Due to the good bonding nature of ceramic materials with cement it increases the strength of the concrete with respect to the increase of CFA material. The durability properties of concrete also seems to be performed well because, the CFA materials are consist of good chemical resistance nature. From the study it is found that the percentage of replacement for FA with CFA material is 20%, within which the performance of CFA concrete is better and all the results are attained within the design limit and it help to solve the disposal problem to the environment.Â Â